How can Juul balance eliminating sales to minors while offering adults tobacco flavored products? - Osland, Asbjorn; Clinch, Nanette (London : SAGE Publications: SAGE Business Cases Originals, 2020)
Juul designed products for adults who wanted to quit smoking. It eliminated some flavors that appeared to target children, while maintaining those that adults wanted. Even this may not have been enough—President Trump wanted the Food and Drug Administration (FDA) to force e-cigarette vendors to limit offerings to tobacco flavors. The FDA and other public health organizations called teen vaping an epidemic, citing the danger of nicotine use as damaging to teen brain development, with addiction to nicotine potentially leading to smoking cigarettes. The FDA and Juul had previously agreed that Juul had to take action. Juul curtailed sales to minors through restrictions on sales outlets, monitored Internet sales, and excluded additional flavors. Yet, as Juul attempted to meet FDA requirements, the vaping epidemic continued. Juul now seeks to manage the tension between achieving commercial success by helping adults with smoking cessation while satisfying FDA regulations, including the likely ban on non-tobacco flavors.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Juul -- Case studies; Smoking cessation products industry -- Case studies; Electronic cigarettes -- Social aspects -- Case studies; Youth -- Drug use -- Case studies